Why read Machiavelli? (2013)
Este documento contiene en texto completo el articulo Why read Machiavelli? publicado en Desafíos; Vol. 25, Núm. 2 (2013): (julio-diciembre) Maquiavelo; 9-11;2145-5112;0124-4035